2022
DOI: 10.1002/app.52429
|View full text |Cite
|
Sign up to set email alerts
|

Tuning adhesion performance of an acrylic pressure‐sensitive adhesive using polysilsesquioxane‐acrylic core‐shell nanoparticles

Abstract: Surface migration of unmodified inorganic or polymer core‐inorganic shell nanoparticles has limited their application for improvement of pressure‐sensitive adhesives (PSAs) properties. The efficiency of utilization of modified inorganic nanoparticles with sticky polymer brushes was investigated to overcome this problem. For this purpose, polymethacryloxypropylsilsesquioxane‐acrylic core‐shell (CS) nanoparticles were synthesized and added to poly(methyl methacrylate‐co‐butyl acrylate) (MBC) acrylic PSA through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 50 publications
(138 reference statements)
0
6
0
Order By: Relevance
“…4,5 PSAs are soft viscoelastic materials that are capable of adhering to most surfaces under short contact time and low contact pressure while dissipating considerable energy during debonding. 6,7 Kaelble showed that the main reason for the proper adhesion of the PSAs is the occurrence of microcavitation and fibrillation during the debonding process. 8 To be specific, the PSAs in which microcavities form at the interface between the adhesive and the substrate during the debonding, followed by their expansion into the adhesive bulk to form fibrils, are capable of considerable energy dissipation.…”
Section: ■ Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…4,5 PSAs are soft viscoelastic materials that are capable of adhering to most surfaces under short contact time and low contact pressure while dissipating considerable energy during debonding. 6,7 Kaelble showed that the main reason for the proper adhesion of the PSAs is the occurrence of microcavitation and fibrillation during the debonding process. 8 To be specific, the PSAs in which microcavities form at the interface between the adhesive and the substrate during the debonding, followed by their expansion into the adhesive bulk to form fibrils, are capable of considerable energy dissipation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…4,10 These properties, frequently evaluated by the static shear test, 13 are important in applications where a PSA must withstand moderate levels of stress for a long time such as in bonding digital camera parts. 10 Approaches like taking advantage of nanoparticles, 6 comonomers (such as acrylic acid (AA), methyl methacrylate (MMA), styrene (St), etc. ), 4,14,15 and cross-linking agents 14 are used to improve the creep resistance of acrylic PSAs.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The available physicochemical methods for the synthesis of nanoparticles are relatively expensive and toxic and also cause harmful effects on the nature (Ahmadi- Dehnoei & Ghasemirad, 2022;Naveenraj et al, 2018). In this regard, green synthesizing procedures implicate the usage of natural materials, such as plant (Dousari et al, 2023;Indhira et al, 2022), fungal (Ameen, al-Homaidan, et al, 2021), algae (AlNadhari et al, 2021) and bacteria (Ameen et al, 2020) extracts, to act as the trapping and reducing agents in combination with metals similar to nickel, which can merge into an interesting and valuable field in nanotechnology (Dehnoei & Ghasemirad, 2020).…”
Section: Introductionmentioning
confidence: 99%